Blame it on the injury: Trauma is a risk factor for pancreatic fistula following distal pancreatectomy compared with elective resection. Issue 6 (December 2019) - Rozich, Noah S.; Morris, Katherine T.; Garwe, Tabitha; Sarwar, Zoona; Landmann, Alessandra; Siems, Chesney B.; Jones, Alexandra; Butler, Casey S.; McGaha, Paul K.; Axtman, Benjamin C.; Edil, Barish H.; Lees, Jason S.
Abstract : BACKGROUND: Postoperative pancreatic fistula (POPF) remains a significant source of morbidity following distal pancreatectomy (DP). There is a lack of information regarding the impact of trauma on POPF rates when compared with elective resection. We hypothesize that trauma will be a significant risk factor for the development of POPF following DP. METHODS: A retrospective, single-institution review of all patients undergoing DP from 1999 to 2017 was performed. Outcomes were compared between patients undergoing DP for traumatic injury to those undergoing elective resection. Univariate and multivariable analyses were performed using SAS (version 9.4). RESULTS: Of the 372 patients who underwent DP during the study period, 298 met inclusion criteria: 38 DPs for trauma (TDP), 260 elective DPs (EDP). Clinically significant grade B or C POPFs occurred in 17 (44.7%) of 38 TDPs compared with 41 (15.8%) of 260 EDPs ( p < 0.0001). On multivariable analysis, traumatic injury was found to be independently predictive of developing a grade B or C POPF (odds ratio, 4.3; 95% confidence interval, 2.10–8.89). Age, sex, and wound infection were highly correlated with traumatic etiology and therefore were not retained in the multivariable model. When analyzing risk factors for each group (trauma vs. elective) separately, we found that TDP patients who developed POPFs had less sutured closure of their duct, higher infectious complications, and longer hospital stays, while EDP patients that suffered POPFs were more likely to be male, younger in age, and at a greater risk for infectious complications. Lastly, in a subgroup analysis involving only patients with drains left postoperatively, trauma was an independent predictor of any grade of fistula (A, B, or C) compared with elective DP (odds ratio, 8.6; 95% confidence interval, 3.09–24.15), suggesting that traumatic injury is risk factor for pancreatic stump closure disruption following DP. CONCLUSION: To our knowledge, this study represents the largest cohort of patients comparing pancreatic leak rates in traumatic versus elective DP, and demonstrates that traumatic injury is an independent risk factor for developing an ISGPF grade B or C pancreatic fistula following DP. LEVEL OF EVIDENCE: Prognostic study, Therapeutic, level III.